Cardiovascular responses during an indoor race walking competition - Vernillo, G.; Agnello, L.; Drake, A.; Fiorella, P.; Piacentini, M. F.; La Torre, A. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: This study aims to examine the cardiovascular responses during an indoor race walking competition over the distance of 3-km for female and 5-km for male athletes. METHODS: During the Italian indoor RW Championship heart rate was monitored on eleven well trained race walkers (five men and six women) and then refereed as percentages of individuals` theoretical maximum heart rate (206-0.7·age). To provide a measure of relative intensity, five HR zones were assessed. Alterations in % HRmax both for the five and three 1000-m split distances were determined. RESULTS: During the 5-km race the athletes spent 79.7% (15 min 45 s) at HR5 (i.e., 90-100% of HRmax). Specifically, % HRmax increased by 10% in the last compared to the first 1000-m sector (P=0.006, effect size = 2.47±0.83, very large), with the first 1000-m sector lower than the subsequent ones (P=0.01, effect size=2.17 to 2.47, very large). While, for the 3-km the athletes spent 86.9% (11 min 35 s) at HR5 (i.e., 90-100% of HRmax) with no differences observed in the % HRmax between the three 1000-m sectors (P>0.01). CONCLUSION: The dissemination of performance and physical attributes identified within the present study reveal that the exercise intensity of indoor race walking competitions has a high-intensity profile and will assist coaches and athletes in formulating appropriate training, competition and recovery.